HBsAg loss after peginterferon‐nucleotide combination treatment in chronic hepatitis B patients: 5 years of follow‐up. Issue 12 (29th July 2017) - Stelma, F.; van der Ree, M. H.; Jansen, L.; Peters, M. W.; Janssen, H. L. A.; Zaaijer, H. L.; Takkenberg, R. Bart; Reesink, H. W.
Summary: Combining peginterferon‐alfa‐2a (pegIFN) with a nucleotide analogue can result in higher rates of HBsAg loss than either therapy given alone. Here, we investigated the durability of the response to combination therapy in chronic hepatitis B (CHB) patients after 5 years of follow‐up. In the initial study, 92 CHB patients (44 HBeAg‐positive, 48 HBeAg‐negative) with HBV DNA >100 000 c/mL (~20 000 IU/mL) and active hepatitis were treated for 48 weeks with pegIFN 180 μg/week and 10 mg adefovir dipivoxil daily. For the long‐term follow‐up (LTFU) study, patients were followed up for 5 years after the end of treatment. At year 5, 70 (32 HBeAg‐positive, 38 HBeAg‐negative) patients remained in the study. At year 5, 19% (6/32) of HBeAg‐positive patients and 16% (6/38) of HBeAg‐negative patients lost HBsAg, and no HBsAg seroreversion was observed. The 5‐year cumulative Kaplan‐Meier estimate for HBsAg loss was 17.2% for HBeAg‐positive patients and 19.3% for HBeAg‐negative patients. Fourteen of sixteen patients who lost HBsAg at any time point during follow‐up developed anti‐HBs antibodies (>10 IU/L). At year 5, in total 63% (20/32) of HBeAg‐positive and 71% (27/38) of HBeAg‐negative patients were retreated with nucleos(t)ide analogues during follow‐up. The cumulative Kaplan‐Meier estimate for retreatment was 60% of patients at year 5. At year 5 of follow‐up, 18% of CHB patients treated with pegIFN/nucleotide analogue combination therapy had durable HBsAg loss and 88% of these had developed anti‐HBs antibodies.